Work-Related Factors Associated With Burnout Among Peruvian Nurses - Caleb Sucapuca; Wilter C. Morales-García; Jacksaint Saintila (SAGE Publishing, 2022)
Introduction: Commonly, burnout in nurses has influenced their performance. The contribution of this study allows to broaden the knowledge of the performance-burnout relationship and identifies the work performance in nurses as a precursor of burnout. Objective: The study aimed to examine the factors of work performance of nursing staff that influence burnout. Methods: A descriptive cross-sectional design was used and a total of 340 nurses from the department of Puno in Peru participated. Demographic, job performance, and burnout data were collected. Results: Job performance factors, such as counterproductive behavior, positively influenced burnout, while task and context performance negatively influenced burnout. These variables explained 28.54% of the variance of burnout among nurses. Conclusion: Job performance factors have a significant impact on burnout. To reduce burnout, workforce resources that motivate, engage, and monitor nurse performance must be identified individually or organizationally. There is a need to develop training that promotes the improvement of emotional skills for better performance and the reduction of professional burnout.